(untitled) - Hunter, Erin (New York, NY, 2023)
"With RiverClan in crisis, ShadowClan and its leader Tigerstar step in to offer their help-whether RiverClan wants it or not"--
Keywords: Fiction; Clans; Fiction; Cats; Juvenile fiction; Clans; Juvenile fiction; Cats; Fantasy fiction; Animal fiction; Novels